The effects of peer support group on promoting quality of life in patients with breast cancer - Taleghani, Fariba (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: The tragedy of having breast cancer can cause many challenges for women. Patients seek for someone to compare their emotional and physical reactions with. This study was conducted to evaluate the impact of implementation of peer support group on the quality of life of breast cancer patients. MATERIALS AND METHODS: This clinical trial was conducted on patients who underwent modified radical mastectomy and/or lumpectomy in surgical wards of Isfahan and Tehran (2 cities in Iran). The members of the peer group were trained after they volunteered to enter the study and their capacity was evaluated. They started contacting the patients after the surgery and continued it during treatments and several months after completion of the treatments. Patients were placed in 2 groups of case and control by simple random sampling. The quality of life of patients in both groups was measured during and after the completion of treatment using standard instruments of National Medical Center and Beckman Research Institute. FINDINGS: The mean score of the physical dimension of life quality in the case and control groups in Tehran had a significant difference during 2 stages. There was no significant difference between the mean scores of physical dimension of life quality between the 2 groups during the 2 stages in Isfahan. Moreover, the mean scores of mental dimension of the quality of life showed a significant difference between the 2 groups in Tehran during the 2 stages. The mean scores were also significantly different during the second stage in Isfahan. There was a significant difference between the social dimension of quality of life between the 2 groups in Isfahan (p = 0.001). The mean scores of the social dimension of quality of life had significant differences between the 2 groups in Tehran during the 2 stages (p < 0.001). There was a significant difference between the 2 groups regarding the mean score of spiritual dimension of quality of life in Tehran (p < 0.001). CONCLUSIONS: The results showed that patients supported by a peer group enjoyed a higher quality of life compared to others. Although significant differences were observed in scores of both case and control groups in Tehran, similar findings were not obtained in Isfahan. This may be due to incomplete matching of the peer group members and incapability of the volunteers to maintain an effective and constructive communication with the patients.